(untitled) (Journal of Global Arts Studies, 2025)
Background： In the National Trend 3.0 era, commercializing traditional culture is key. While foreign influences challenge traditional dance, “Only This Green”—a dance-poetry drama inspired by “Thousand Miles of Rivers and Mountains”—offers a modern "green-and-blue landscape" interpretation. This integrates cultural confidence with commercialization, providing a vital case study for brand-oriented traditional art IP. Objective： This study explores how brand management strategies drive the commercial value transformation of cultural IP, analyzing “Only This Green” to understand brand management’s role in traditional artistic and cultural IP commercialization. Methods: Based on 8P marketing and SWOT matrix theories, this paper constructs a three-dimensional commercialization model of “positioning-communication-extension”, using case study to analyze Only This Green’s practices in positioning, communication and value extension. Results: “Only This Green” successfully achieved contemporary traditional art expression and commercial value conversion. This was accomplished through precise positioning as “cultural relic IP+artistic innovation,” an “online-offline integration+cross-industry collaboration” communication matrix, and diversified extension strategies (cultural products, tourism). Its success highlights brand management’s critical role in synergistically developing cultural and commercial value. Conclusion: Commercializing traditional cultural IP must center on artistic value, leveraging brand management strategies to create a “cultural core-commercial monetization” closed-loop. This study offers a replicable framework for traditional art IP commercialization and expands brand management theory applications in the cultural and creative industry.